Izobraževalne potrebe ponudnikov zasebnih turističnih nastanitev v Sloveniji - Balažič, Gregor (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2017)
The ROOMS to VET project has carried out a survey among private providers of tourist accommodation in Slovenia. Through interviews were identified general problems and needs in the field of education. The results show that the most problematic is legislation, in that the providers are burdened with the necessity of knowing all the fine points of labyrinthine legislation. Providers are aware of the importance of education and underline the lack of organized education, the lack of links between tourism providers and insufficient knowledge in the usage of various online tools.
Keywords: education; hoteli; hotelirstvo; izobraževanje; Slovenia; Slovenija; turistična geografija; turistična ponudba